Interaction of different metal ions with carboxylic acid group: a quantitative study - Bala, Tanushree; Bhagavatula L. V. Prasad; Sastry, Murali; Kahaly, Mousumi Upadhyay; Waghmare, Umesh V. (Journal of Physical Chemistry A, 2007)
The binding strength of the carboxylic acid group (-COOH) with different divalent metal ions displays considerable variation in arachidic acid (AA) thin films. It is considered that in AA thin films the metal ions straddle the hydrophilic regions of the stacked bilayers of AA molecules via formation of carboxylates. In this study first the uptake of different divalent cations in films of AA is estimated by atomic absorption spectroscopy (AAS). Through the amount of cation uptake, it is found that the strength of binding of different cations varies as Ca2+ > Co2+ > Pb2+ > Cd2+. Variation in the binding strength of different ions is also manifested in experiments where AA thin films are exposed to metal ion mixtures. The higher binding strength of AA with certain metal ions when exposed individually, as well as the preference over the other metal ions when exposed to mixtures, reveal some interesting deviation from the expected behavior based on considerations of ionic radii. For example, Pb2+ is always found to bind to AA much more strongly than Cd2+ even though the latter has smaller ionic radius, indicating that other factors also play an important role in governing the binding strength trends apart from the effects of ionic radii. Then, to get a more meaningful knowledge regarding the binding capability, first-principles calculations based on density functional theory have been applied to study the interaction of different cations with the simplest carboxylic acid, acetic acid, that can result in formation of metal diacetates. Their electronic and molecular structures, cohesive energies, and stiffness of the local potential energy well at the cation (M) site are determined and attempts are made to understand the diversity in geometry and the properties of binding of different metal ions with -COOH group. We find that the calculated M−O bond energies depend sensitively on the chemistry of M atom and follow the experimentally observed trends quite accurately. The trends in M−O bond energies and hence the total M−acetate binding energy trends can actually be related to their molecular structures that fall into different categories:  Ca and Cd have tetrahedral coordination; Fe, Ni, and Co exhibit planar 4-fold coordination; and Pb is off-centered from the planar structure (forming pyramidal structure) due to its stereochemically active lone pair of electrons.

Sensing behavior of atomically thin-layered MoS2 transistors - Late, Dattatray J.; Huang, Yi-Kai; Liu, Bin; Acharya, Jagaran; Shirodkar, Sharmila N.; Luo, Jiajun; Yan, Aiming; Charles, Daniel; Waghmare, Umesh V.; Dravid, Vinayak P.; Rao, C. N. R. (ACS Nano, 2013)
Most of recent research on layered chalcogenides is understandably focused on single atomic layers. However, it is unclear if single-layer units are the most ideal structures for enhanced gas solid interactions. To probe this issue further, we have prepared large-area MoS2 sheets ranging from single to multiple layers on 300 nm SiO2/Si substrates using the micromechanical exfoliation method. The thickness and layering of the sheets were identified by optical microscope, invoking recently reported specific optical color contrast, and further confirmed by AFM and Raman spectroscopy. The MoS2 transistors with different thicknesses were assessed for gas-sensing performances with exposure to NO2, NH3, and humidity in different conditions such as gate bias and light Irradiation. The results show that, compared to the single-layer counterpart, transistors of few MoS2 layers exhibit excellent sensitivity, recovery, and ability to be manipulated by gate bias and green light. Further, our ab initio DFT calculations on single-layer and bilayer MoS2 show that the charge transfer is the reason for the decrease in resistance in the presence of applied field.

Thermal expansion, anharmonicity and temperature-dependent Raman spectra of single- and few-layer MoSe2 and WSe2 - Late, Dattatray J.; Shirodkar, Sharmila N.; Waghmare, Umesh V.; Dravid, Vinayak P.; Rao, C. N. R. (ChemPhysChem, 2014)
We report the temperature-dependent Raman spectra of single-and few-layer MoSe2 and WSe2 in the range 77-700 K. We observed linear variation in the peak positions and widths of the bands arising from contributions of anharmonicity and thermal expansion. After characterization using atomic force microscopy and high-resolution transmission electron microscopy, the temperature coefficients of the Raman modes were determined. Interestingly, the temperature coefficient of the A(2u)(2) mode is larger than that of the A(1g) mode, the latter being much smaller than the corresponding temperature coefficients of the same mode in single-layer MoS2 and of the G band of graphene. The temperature coefficients of the two modes in single-layer MoSe2 are larger than those of the same modes in single-layer WSe2. We have estimated thermal expansion coefficients and temperature dependence of the vibrational frequencies of MoS2 and MoSe2 within a quasi-harmonic approximation, with inputs from first-principles calculations based on density functional theory. We show that the contrasting temperature dependence of the Raman-active mode A(1g) in MoS2 and MoSe2 arises essentially from the difference in their strainphonon coupling.

Combined experimental and theoretical study of the structural, electronic and vibrational properties of bulk and few-layer Td-WTe2 - Jana, Manoj K.; Singh, Anjali; Late, Dattatray J.; Rajamathi, Catherine R.; Biswas, Kanishka; Felser, Claudia; Waghmare, Umesh V.; Rao, C. N. R. (Journal of Physics-Condensed Matter, 2015)
The recent discovery of non-saturating giant positive magnetoresistance has aroused much interest in Td-WTe2. We have investigated structural, electronic and vibrational properties of bulk and few-layer Td-WTe2 experimentally and theoretically. Spin-orbit coupling is found to govern the semi-metallic character of Td-WTe2 and its structural link with the metallic 1 T form provides an understanding of its structural stability. There is a metal-to-insulator switch-over in the electrical conductivity and a change in the sign of the Seebeck coefficient around 373 K. Lattice vibrations of Td-WTe2 have been analyzed using first-principles calculations. Out of the 33 possible zone-center Raman active modes, five distinct Raman bands are observed around 112, 118, 134, 165 and 212 cm(-1) in bulk Td-WTe2. Based on symmetry analysis and calculated Raman tensors, we assign the intense bands at 165 cm(-1) and 212 cm(-1) to the A(1)' and A(1)'' modes, respectively. Most of the Raman bands stiffen with decreasing thickness, and the ratio of the integrated intensities of the A(1)'' to A(1)' bands decreases in the few-layer sample, while all the bands soften in both the bulk and few-layer samples with increasing temperature.
Keywords: Raman spectroscopy; Td-structure; tungsten ditelluride

Electronic structure and properties of layered gallium telluride - Shenoy, U. Sandhya; Gupta, Uttam; Narang, Deepa S.; Late, Dattatray J.; Waghmare, Umesh V.; Rao, C. N. R. (Chemical Physics Letters, 2016)
Layer-dependent electronic structure and properties of gallium monochalcogenides, GaX where X=S, Se, Te, have been investigated using first-principles calculations based on various functionals, with a motivation to assess their use in photocatalytic water splitting. Since hydrogen evolution by water splitting using visible light provides a promising way for solar energy conversion, both theoretical and experimental studies have been carried out on the photochemical hydrogen evolution by GaTe. We also present the Raman spectra of GaTe examined by both theory and experiment. (C) 2016 Elsevier B.V. All rights reserved.